Walt Disney’s Movie Soundtracks as Media in Developing Character Education for Children - FA Wisnu Wirawan; Prima Dona Hapsari (Institut Seni Indonesia Yogyakarta, 2018)
As a medium of communication, a song has a great impact on children’s development. A small number of children song generate children to sing adult songs, however, there are some adult songs which are not suitable the children in relation to lyrics and theme. The incomprehension of the lyrics and meaning existed in the song can be psychologically influential for the child’s development. This study analyzes the role of Walt Disney’s cartoon soundtracks for character education to children. This is a qualitative-descriptive research, taking observation and in-depth interview to 10 informants who have children of 7-11 years old in Yogyakarta, Indonesia. The results stated that the soundtracks How Far I’ll Go and Let It Go bring positive characters in contents that are useful for character education. The character education taken from lyrics of the songs is conveyed and developed by vocabulary enrichment, the discussion in easy-digested language, and storytelling. These require special time. The good changes in children’s good characters happen by time and process. Therefore, character education needs to be continued and developed in different ways.